A Novel Ferroptosis-Related Biomarker Signature to Predict Overall Survival of Esophageal Squamous Cell Carcinoma - Song, Jiahang; Liu, Yanhu; Guan, Xiang; Zhang, Xun; Yu, Wenda; Li, Qingguo (Frontiers in Molecular Biosciences, 2021)
Esophageal squamous cell carcinoma (ESCC) accounts for the main esophageal cancer (ESCA) type, which is also associated with the greatest malignant grade and low survival rates worldwide. Ferroptosis is recently discovered as a kind of programmed cell death, which is indicated in various reports to be involved in the regulation of tumor biological behaviors. This work focused on the comprehensive evaluation of the association between ferroptosis-related genes (FRGs) expression profiles and prognosis in ESCC patients based on The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). ALOX12, ALOX12B, ANGPTL7, DRD4, MAPK9, SLC38A1, and ZNF419 were selected to develop a novel ferroptosis-related gene signature for GEO and TCGA cohorts. The prognostic risk model exactly classified patients who had diverse survival outcomes. In addition, this study identified ferroptosis-related signature as the factor to independently predict the risk of ESCC. Thereafter, we also constructed the prognosis nomogram by incorporating clinical factors and risk score and the calibration plots illustrated good prognostic performance. Moreover, the association of risk score with immune checkpoints was observed. Collectively, our proposed ferroptosis-related gene signature in our study is effective and have a potential clinical application to predict the prognosis of ESCC.